2020
DOI: 10.1007/s10811-019-02020-3
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry

Abstract: Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 63 publications
0
39
0
2
Order By: Relevance
“…These challenges included (1) inconsistent terminology for the inclusion of seaweeds in regulatory frameworks, (2) limited guidance for the responsibility of implementation of biosecurity measures, (3) insufficient evidence to develop disease and pest-specific policies and (4) lack of a coherent approach to seaweed biosecurity risk management in international policies. The report of Kambey et al (2020) and Mateo et al (2020) demonstrated similar issues, as far as national biosecurity-related regulations and policies were concerned in Indonesia and the Philippines, respectively. These issues included (1) a lack of a "recognized" national authority to enforce regulations;…”
Section: Introductionmentioning
confidence: 84%
“…These challenges included (1) inconsistent terminology for the inclusion of seaweeds in regulatory frameworks, (2) limited guidance for the responsibility of implementation of biosecurity measures, (3) insufficient evidence to develop disease and pest-specific policies and (4) lack of a coherent approach to seaweed biosecurity risk management in international policies. The report of Kambey et al (2020) and Mateo et al (2020) demonstrated similar issues, as far as national biosecurity-related regulations and policies were concerned in Indonesia and the Philippines, respectively. These issues included (1) a lack of a "recognized" national authority to enforce regulations;…”
Section: Introductionmentioning
confidence: 84%
“…In order to understand the scope and objectives of selected biosecurity frameworks, five "themes" were analysed based on methods used by Campbell et al (2019a) and Kambey et al (2020). The themes included the force of the framework, the terminology used for the inclusion of seaweed aquaculture, the approach taken to implement biosecurity measures, the information type used to inform the text and the inclusion of the precautionary approach.…”
Section: Thematic Analysismentioning
confidence: 99%
“…The biosecurity risks associated with seaweed farming in Tanzania were identified in the framework texts, using a list of categorised risks, as listed in Campbell et al (2019a) and Kambey et al (2020). Risks were identified in texts of the frameworks, and quantified under five categories including ecological, environmental, ecosystem, economic, social and farmer welfare.…”
Section: Inclusion Of Biosecurity Risks In Texts Of Frameworkmentioning
confidence: 99%
See 2 more Smart Citations